Role of nursing professionals for parenting development in early childhood: a systematic review of scope - Kesley de Oliveira Reticena; Vânia do Nascimento Tolentino Yabuchi; Maria Fernanda Pereira Gomes; Lucíola D'Emery Siqueira; Flávia Corrêa Porto de Abreu; Lislaine Aparecida Fracolli (Universidade de São Paulo, 2019)
Objective: map available evidence regarding the role of nursing professionals in early childhood care through the development of parenting. Method: systematic review of scope, with selection of studies about the role of nursing professionals for the development of parenting in the context of early childhood care, using a standardized data extraction tool and qualitative thematic analysis. Results: nineteen studies were included, showing the role of nursing professionals covers nine dimensions: promoter of parental role construction; guidance and support for the implementation of physical health care; guidance for promoting safe environment; application of theories, principles and methods of maternal and child programs; development of therapeutic relationships; implementation of maternal and child care management; promotion of access to support network; guidance for the life course of parental figures; and use of scientific evidence to guide practice. Conclusion: nursing professionals offer important knowledge and significant practices for the development of parenting in early childhood care. These findings provide the basis for improving the clinical practice of these professionals, showing relevant areas of action and interventions to early childhood.